Regional specification and complementation with non-neuroectodermal cells in human brain organoids - Tanaka, Yoshiaki (J Mol Med (Berl), 2021)
Along with emergence of the organoids, their application in biomedical research has been currently one of the most fascinating themes. For the past few years, scientists have made significant contributions to deriving organoids representing the whole brain and specific brain regions. Coupled with somatic cell reprogramming and CRISPR/Cas9 editing, the organoid technologies were applied for disease modeling and drug screening. The methods to develop organoids further improved for rapid and efficient generation of cerebral organoids. Additionally, refining the methods to develop the regionally specified brain organoids enabled the investigation of development and interaction of the specific brain regions. Recent studies started resolving the issue in the lack of non-neuroectodermal cells in brain organoids, including vascular endothelial cells and microglia, which play fundamental roles in neurodevelopment and are involved in the pathophysiology of acute and chronic neural disorders. In this review, we highlight recent advances of neuronal organoid technologies, focusing on the region-specific brain organoids and complementation with endothelial cells and microglia, and discuss their potential applications to neuronal diseases.